Early Intervention for Young Children with Autism Spectrum Disorder - Lang, Russell; Hancock, Terry B.; Singh, Nirbhay N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book examines early intensive behavioral intervention (EIBI) programs for young children with autism spectrum disorder (ASD). It analyzes current research on early intervention (EI) and explains the importance of accurate, timely detection of ASD in facilitating the use of EI. Chapters address five widely researched EIBI approaches: Discrete Trial Training, Pivotal Response Training, the Early Start Denver Model, Prelinguistic Milieu Teaching, and Enhanced Milieu Teaching. This in-depth study of current EIBI approaches offers a rigorous guide to earlier and more intensive interventions for children with ASD, leading to greater autonomy and improved later life outcomes for individuals. Featured topics include: Parent-implemented interventions and related issues. Evaluations of controversial interventions used with children with ASD. Factors contributing to rising ASD prevalence. Obstacles to obtaining accurate ASD diagnosis in young children. Early Intervention for Young Children with Autism Spectrum Disorder is an essential resource for researchers, clinicians, and graduate students in developmental, clinical child, and school psychology, behavioral therapy/rehabilitation, social work, public health, educational policy and politics, and related psychology and behavioral health fields.
Overview of Early Intensive Behavioral Intervention for Children with Autism Spectrum Disorder -- Early Diagnostic Assessment for Autism Spectrum Disorder -- Discrete Trial Training -- Pivotal Response Treatment -- Early Start Denver Model -- Prelinguistic Milieu Teaching -- Enhanced Milieu Teaching -- Training Parents to Implement Early Interventions to Children with Autism Spectrum Disorder -- Fad, Pseudoscientific and Controversial Interventions.
Keywords: Psychology; Behavioral therapy; Social work; Developmental psychology; Psychology; Developmental Psychology; Behavioral Therapy; Social Work; Electronic books